Sampling and analysis of substances and substance mixtures which may occur simultaneously as vapours and particles in workplace air [Air Monitoring Methods, 2018]. Issue 3 (26th July 2018) - Breuer, D.; Dragan, C.G.; Hebisch, R.; Bartsch, R.; Giesen, Y.; Krämer, W.; Nitschke, L.; Nitz, G.; Pannwitz, K.‐H.; Tschickardt, M.; Brock, T.H.; Hartwig, A.; et al.
Abstract: Due to their physical properties semi‐volatile substances can occur as particle/vapour mixtures in workplace air. Such mixtures are formed, e.g. as a result of mechanical processes such as the processing of metals or ceramics, during dipping processes in electroplating or during spraying processes. For that reason workplace air measurements must be carried out with a suitable sampling system for the collection of particles and vapours in workplace air. This report sets out the general principles of the physical behaviour of airborne aerosols and explains the different toxic effects of both phases by inhalation. Sampling strategies for collection of particle/vapour mixtures in workplace air using generally accepted combined sampling systems are described. In addition, several approved sampling heads and sampling systems such as GSP, GSP‐Mini, GGP/GGP‐U are presented. Influences on the measurement results such as temperature, humidity, sampling, transport and storage are discussed and the calculation of the expanded uncertainty when measuring these special kinds of substances is explained. Joint Publication of the Analytical Subcommittee of the Chemistry Board of Experts of the Expert Committee Raw Materials and Chemical Industry of the German Social Accident Insurance and the working Group "Air Analyses" of the Permanent Senate Commission of the DFG for the Investigation of Health Hazards of Chemical Compounds in the Work Area.